Seasonal variation and intra urban heterogeneity of the entomological risk of transmission of dengue and yellow fever in Abidjan, Côte d'Ivoire. Issue 3 (30th March 2022) - Guindo‐Coulibaly, Négnorogo; Kpan, Mintokapieu Didier Stephane; Adja, Akré Maurice; Kouadio, Affoué Mireille Nadia; Assouho, Konan Fabrice; Zoh, Dounin Danielle; Azongnibo, Konan Rodolphe Mardoché; Remoue, Franck; Fournet, Florence
Abstract: Dengue and yellow fever are prevalent in Côte d'Ivoire and Aedes ( Stegomyia ) aegypti (Linnaeus), (Diptera: Culicidae), is known as the main vector. We aimed to assess seasonal variation and spatial heterogeneity in the transmission of both arbovirus diseases in Abidjan. Entomological surveys targeting larvae of A. aegypti, were carried out between November 2015 and August 2016 covering the four climatic seasons including a cohort of 100 houses randomly selected in three neighbourhoods. A. aegypti was the predominant species (96.6%) of mosquitoes resulting from the rearing of harvested larvae, and the only vector of dengue and yellow fever recorded during the study period. The highest proportion of water storage containers (45.5%) which represented the major breeding sites infested by the larvae of A. aegypti, was observed in Anoumabo. The house indices >5% and/or Breteau indices >20 recorded in each neighbourhood, during the different climatic seasons, indicated that there was, a high and permanent, heterogeneity in the transmission risk of dengue and yellow fever between the three neighbourhoods. In terms of transmission risk, Anoumabo was the neighbourhood with the highest risk compared to the two others, then, particular attention should be paid to this site in terms of surveillance by vector control programme in Abidjan. Abstract : Aedes aegypti is the only vector of arboviruses with more than 96% of the mosquitoes collected in the neighbourhoods of Anoumabo, Bromakoté and Petit‐Bassam in Abidjan city. The water storage tanks and the used tires are the most frequently positive breeding sites in the three neighbourhoods of Abidjan in all seasons. The estimated larval indices indicate a high risk for entomological transmission of Dengue and Yellow fever with the highest values in the neighbourhood of Anoumabo. Entomological risk indices for yellow fever and dengue in Abidjan, Côte d'Ivoire.